Ingestions Alimentaires Et Performances De Production Et De Reproduction Des Lapines (Oryctolagus Cuniculus) Gestantes Nourries Avec Des Aliments Contenant Des Feuilles De Neem (Azadirachta Indica) - S., Soumanou Toleba; Dahouda, Mahamadou; Vidjannagni, Sévérin D.; Sina, Haziz; Natonnagnon, Ulrich; Harouna, Aminatou; Adenile, Adam D.; Anagonou, Nadine S. I.; Baba-Moussa, Lamine (European Scientific Journal, ESJ, 2017)
This study was conducted as part of a series of experiments on the use of dried leaves for the production of complete rabbit feed. For this purpose, 120 female rabbits, distributed in 4 batches (N0, N5, N10 and N15) with the same number (30) and homogeneous average weights (2595 g to 2708.7 g) were followed before and during pregnancy. Each of the 4 lot were composed, in the same proportion, of nulliparous and multiparous females. Those animals were subjected to four Azadirachta indica leaves based foods in different proportions: N0: 0%; N5: 5%; N10: 10% and N15: 15%. Our data shows that the gestation rates were as follows for the four lots: N0 (90%), N5 (80%) and N10 (90%) and N15 (76.67%). Except a single female from lot N10, all females were pregnant and gave birth. No significant difference (P> 0.05) was found between the mean of total daily consumptions among the pregnant rabbits of the four batches that ranged from 169.40 to 198.31 g / d. The average litters of the batches N0 (5.33 rabbits / mother), N5 (6.5 rabbits / mother) and N10 (5.61 rabbits / mother) were similar (P> 0.05) but higher (P 0.05). On the other hand, no difference (P> 0.05) was observed between the average weights of the rabbits of the control batch N0 (59.06 g) and those of N5 and N15.